Investigation on rapidly mutating Y-STRs multiplex in Indian population: A pilot study. Issue 1 (December 2019) - Shrivastava, Pankaj; Alghafri, Rashed; Almheiri, Reem; Mishra, Aditi; Alfalasi, Hamda; Khoory, Sarah; Damji, Ruksar; Kishan Kumawat, Ram; Kumar Choudhary, Sumit; Dixit, Shivani; Kaitholia, Kamlesh; Ranjan Dash, Hirak; et al.
Abstract: Importance of rapidly mutating (RM) Y- STRs) is already established and is evident with the addition of seven RM Y-STR markers in new generation Yfiler Plus (YFP) multiplex system. Performance of the 7 RM Y-STRs included in YFP is evaluated in central Indian population. We also report here a pilot study on genetic polymorphism using 13 Rapidly Mutating Y STRs (RM Y-STR) on Indian population. Forensic parameters including allele frequencies, gene diversities, discrimination capacity and Haplotype diversity will be calculated for both the amplification assays. Forensic application and kinship analysis will be highlighted in thisstudy.